Analysis of the Influence of Different Processing Methods on the Main Effective Components in Oviductus Ranae by High-Performance Liquid Chromatography with Diode Array Detector - Yang Xu; Xianwen Yue; Jihong Chi; Huailei Yang; Ying Wang; Yongsheng Wang; Peng Yu; Huiwei Bao (Journal of Chemistry)
Oviductus Ranae (OR) is one of the “treasures of Changbai Mountain” in China. It is used clinically for the treatment of infirmity after illness, fatigued spirit, cough, hemoptysis, and so forth. In this study, a simple and sensitive high-performance liquid chromatography-diode array detector (HPLC-DAD) method was developed for the simultaneous determination of five main effective components (1-methyl hydantoin, estradiol, cholesterol, 7-keto-cholesterol, and 4-cholesten-3-one) in OR and its different processed products. The results indicated that these five components showed good linear relationships within their own concentration ranges along with coefficients of determination ≥0.9996. Average recoveries ranged from 97.67% to 100.06%, with RSDs of 1.45%–1.99%. The proposed method was found to be simple, accurate, and stable, which provided an effective analytical method for quality control and evaluation of OR and its different processed products.